(untitled) (Research, Society and Development, 2025)
Implant-supported prosthetic rehabilitation in the smile region represents a significant challenge for the dentist, requiring careful planning that involves the precise positioning of the implant and its harmonious integration with the soft and hard tissues. To achieve satisfactory aesthetic results, it is essential to consider the correct adaptation of restorations, whether direct or indirect, ensuring harmony with the protective periodontium. In this context, adequate manipulation of the gingival tissues, combined with detailed prosthetic work, plays a fundamental role in obtaining the desired emergence profile. This study aims to present a case report on the surgical folding technique for gingival conditioning during reopening, applied to oral rehabilitation, in which the patient was rehabilitated with an implant in the region of element 21. Highlighting the importance of planning from the initial phases with prosthetic provisionals until the final installation of the definitive prosthesis. Intervention in peri-implant tissues can be carried out at different moments during the treatment, including before implant installation, during their placement, throughout the osseointegration period and mainly during the reopening phase, demonstrating the relevance of an integrated approach to achieve a satisfactory aesthetic and functional result.